STUDI KASUS TEKNIK PEMERIKSAAN THORAX PADA ANAK DENGAN TEKNIK KV TINGGI DI INSTALASI RADIOLOGI RSUD DR. R. SOETIJONO BLORA - Fahri An Najih; Ike Ade Nur Liscyaningsih; Widya Mufida (Bajang Institute, 2025)
Background: on examination of the thorax in children in Radiology installation Dr. R. Soetijono Blora used high kV technique that is exposure factor used 60 kV and mAs 1 with patient age 5 months. Projection used Antero-Posterior (AP). Meanwhile, according to the theory of thorax examination of pediatric patients using KV 40, mAs 10 and 42 kV, mAs 1.6 with Antero-Posterior (AP) , Postero-Anterior (PA) and Lateral projections. This study aims to determine the techniques and objectives in the examination of the Thorax in children with high kV techniques. Research Methods: this study uses descriptive qualitative methods with a case study approach. The research was carried out at the radiology installation of Dr Soetijono hospital blora in September 2024 – May 2025. The object in this study is a pediatric patient who underwent thorax examination, with subjects consisting of 3 radiographers and 1 radiology specialist. The method of data collection is observation, documentation interviews and literature studies. Furthermore, the processed data were analyzed in the form of interview transcripts, then a categorization table was made to be reduced. After the data is reduced, the presentation of the data is done in the form of a narrative and then analyzed with a theoretical basis for further conclusions to be drawn. Results: research shows that examination of the Thorax in children in hospital dr. R. Soetijono Blora adjusted to the age and clinical condition of the patient, the projection used Antero-Posterior (AP) with supine patient position, on examination applied high kV technique of 60 kV and 1 mAs. In this examination kVp used in addition to 10 of routine thorax examination in adult patients is 50 KV and mAs 10 while the mAs value is reduced to 1. The purpose of this technique is to minimize the movement of the patient. The use of high kV is expected to produce sharp and informative images, while a small mAs value helps speed up image acquisition thereby reducing the likelihood of artifacts due to movement